Recent Advances in the Direct Electron Transfer-Enabled Enzymatic Fuel Cells - Yu, Sooyoun; Myung, Nosang V. (Frontiers in Chemistry, 2021)
Direct electron transfer (DET), which requires no mediator to shuttle electrons from enzyme active site to the electrode surface, minimizes complexity caused by the mediator and can further enable miniaturization for biocompatible and implantable devices. However, because the redox cofactors are typically deeply embedded in the protein matrix of the enzymes, electrons generated from oxidation reaction cannot easily transfer to the electrode surface. In this review, methods to improve the DET rate for enhancement of enzymatic fuel cell performances are summarized, with a focus on the more recent works (past 10 years). Finally, progress on the application of DET-enabled EFC to some biomedical and implantable devices are reported.